Implementasi gerakan penguatan pendidikan karakter sebagai wahana pendidikan nilai - Aulia, Syifa Siti; Arif, Dikdik Baehaqi; Amalia, Rosidah (Jurnal Pendidikan Karakter, 2022)
This study aims to analyze the implementation of the movement to strengthen character education in terms of 3 aspects policy, implementation, and assessment of the implementation of activities. This research uses a descriptive method with a qualitative approach. The object of the study was the Movement for Strengthening Character Education in Kulon Progo Regency. Data collection uses observation, interview, and documentation techniques. Data analysis using interactive model analysis techniques from Miles and Huberman. The results showed that Kulon Progo district has implemented a systematic comprehensive character education strengthening movement in terms of policy, namely with the issuance of Kulon Progo Regent Regulation Number 65 of 2017 concerning guidelines for the implementation of strengthening character education in education units. The implementation of strengthening character education in Kulon Progo Regency consists of 3 main bases, namely, religion, the practice of Pancasila values, and the culture of humanity. Evaluation is carried out in the concept of monitoring and evaluation carried out through observation (direct observation) to collect data both administrative and supporting records to assess character education strengthening activities carried out by the Youth Education and Sports Office of Kulon Progo District.